Resposta à irrigação e à adubação nitrogenada em cobertura da cultura do girassol - Torres, Rogério Ricalde (2014)
The production of sunflower has as main factor limiting the water deficit is caused by scarcity or by poor rainfall distribution. In scenarios where there is enough water supply, soil fertility becomes limiting, where levels of nitrogen (excess or shortage) plays an important role in the sunflower metabolism. Being the sunflower plant responsive to irrigation and nitrogen fertilization we tried to identify for the region of the Border West of Rio Grande do Sul, the point of greatest crop yield. The experiment was conducted at the Instituto Federal Farroupilha campus Alegrete, Alegrete - RS. The experimental design consisted of randomized blocks subdivided into the space where the first factor (A), four doses of supplemental irrigation (0%, 50%, 75% and 100% of crop evapotranspiration) were tested, and the second factor (B) doses of nitrogen fertilization in covering (0%, 50%, 100% and 150% of the recommendation of soil analysis, according to the Comissão de Química e Fertilidade do Solo, 2004). During the crop cycle the following parameters were evaluated: leaf area index, plant height, stem diameter and dry mass. When the plants reached physiological maturity were evaluated yield components mass of 1000 seeds and productivity, the dry mass. To study conditions there was no significant interaction between treatments for any of the variables. The irrigation depths influenced only in the mass of 1000 seeds with an increment of 6.35 g in the treatment of 100% of ETc, equivalent to 11.75% of the mass obtained in the treatment without irrigation. Possibly, the high rates of precipitation during the cycle no greater crop response . The doses of nitrogen fertilization in covering influence on all variables, especially the doses of 100 and 150% of ROLAS. To study conditions, it is recommended nitrogen fertilization in covering at a dose of 100% of ROLAS, and is not recommended for supplemental irrigation. However, as the conduction period of the experiment was atypical (water excess), it is recommended to study the influence of irrigation in normal years and low rainfall.